The role of oral health‐related quality of life in the association between dental caries and height, weight and BMI among children in Bangladesh. Issue 6 (27th November 2021) - Mishu, Masuma Pervin; Tsakos, Georgios; Heilmann, Anja; Watt, Richard G
Abstract: Objectives: To examine whether oral health‐related quality of life (OHRQoL) explained the negative associations between dental caries and anthropometric measures of child growth among a sample of 5‐ to 9‐year‐old children in Dhaka, Bangladesh, while taking potential confounding factors (maternal education, family income, study setting, child's birth weight and childhood diseases) into account. In addition, to test whether specific oral impacts had a role in explaining these associations. Methods: Data collection was conducted via a cross‐sectional survey among children and their parents from both hospital and school settings in Dhaka. Dental caries and severe consequences of dental caries (defined here as dental sepsis) were the exposure variables, and age‐ and sex‐adjusted height‐z‐scores (HAZ), weight‐z‐scores (WAZ) and BMI‐z‐scores (BAZ) were the outcome variables. OHRQoL was measured using the Bengali version of the Scale of Oral Health Outcomes for 5‐year‐old children (SOHO‐5). First, associations between oral impacts (prevalence of overall impacts and specific items of the SOHO‐5) and outcome measures were assessed. Multiple linear regression was used to assess associations between caries and anthropometric measures, adjusted for potential confounders. Oral impacts were then added to test whether their inclusion attenuated the associations between exposures and outcomes. To further investigate potential mediating role of oral impacts, structural equation modelling (SEM) was used to test the hypothesis that dental caries and sepsis were associated with the outcomes directly and also indirectly via oral impacts in general. A similar approach was used to investigate mediation by specific SOHO‐5 items. Results: The sample consisted of 715 children, 73.1% of whom had dental caries, 37.5% presented with sepsis, and 57.3% reported at least one oral impact (SOHO‐5 score ≥1). Prevalence of overall oral impacts and also the impact on 'eating difficulty' (a specific item of SOHO‐5) were negatively associated with all three outcomes. Dental caries and sepsis was associated with lower HAZ, WAZ and BAZ, and adjustment for overall oral impacts considerably attenuated the associations between 'severe dental caries' and outcomes, and dental sepsis and outcomes. Using SEM, we found significant indirect associations between caries and sepsis and anthropometric measures via oral impacts (except for dental caries and HAZ). Considering specific oral impacts, eating difficulties explained about 44% and 65% of the associations between caries and anthropometric outcomes, and dental sepsis and anthropometric outcomes, respectively. Conclusions: Oral impacts, in particular eating difficulties, appear to mediate associations between caries and markers of child growth among this population.